Immune Characterization of Ovarian Cancer Reveals New Cell Subtypes With Different Prognoses, Immune Risks, and Molecular Mechanisms - Cong, Shanshan; Guo, Qiuyan; Cheng, Yan; He, Yanan; Zhao, Xibo; Kong, Congcong; Ning, Shangwei; Zhang, Guangmei (Frontiers in Cell and Developmental Biology, 2020)
Ovarian cancer (OV) poses an enormous threat to women's lives due to its complicated mechanism and atypical symptom. Exiting various treatments fail to increase the survival rate of OV remarkably. People gradually pay attention to the tumor microenvironment (TME) because of its role in the tumorigenesis and progression of tumors. This research mainly studied the immune characterization of OV by CIBERSORT and MCP-counter. We reclassified OV into four TME cell subtypes with different prognosis and achieved the infiltration situation of these cells in each subtype. The immune risk of diverse subtypes also was evaluated base on the immunoscore calculated by Cox regression analysis. In the meantime, we analyzed the molecular mechanism and hallmark pathways between four subtypes. As a consequence, the immune pro-cancer cell subtype had the worst prognosis, closely related to the high immune risk group and was characterized by the low expression of checkpoints and MHC class I and II molecules, the high expression of hypoxia-related genes, the high expression of EMT pathway and hypoxia pathway, and the low expression of DNA repair pathway and interferon α response pathway. This research contributed to explore the mechanism relating to immune and find more effective immunotherapy targets of OV.